“I hope I don’t die before my child”: The representation of autism in Turkish films - Emin Paftalı; Ayşe Tunç-Paftalı; Gizem Yıldız (CINEJ Cinema Journal)
This study aims to examine how autism is represented in Turkish films. Three films featuring a character with autism were analyzed through document analysis. The following four themes were reached in the study: (1) behaviors specific to autism, (2) the family of the character with autism, (3) society’s perspective on autism, and (4) the representation of the character with autism in the film. Notably, the films focus on the difficulties experienced by the character with autism, the problems experienced in the family, and the difficulties in accepting autism. In addition, all the films have melodramatic structures, and the families of individuals with autism experience much more difficulties than ordinary people.